Roots of a Complex Number

Root of a complex number can be expressed in the standard form A + iB, where A and B are real.

In words we can say that any root of a complex number is a complex number

Let, z = x + iy be a complex number (x ≠ 0, y ≠ 0 are real) and n a positive integer. If the nth root of z be a then,

\(\sqrt[n]{z}\) = a

\(\sqrt[n]{x + iy}\) = a

x + iy = a\(^{n}\)

From the above equation we can clearly understand that

(i) a\(^{n}\) is real when a is purely real quantity and

(ii) a\(^{n}\) is either purely real  or purely imaginary quantity when a is purely imaginary quantity.

We already assumed that, x ≠ 0 and y ≠ 0.

Therefore, equation x + iy = a\(^{n}\) is satisfied if and only if a is an imaginary number of the form A + iB where A ≠ 0and B ≠ 0 are real.

Therefore, any root of a complex number is a complex number.


Solved examples on roots of a complex number:

1. Find the square roots of -15 - 8i.

Solution:

Let \(\sqrt{-15 - 8i}\) = x + iy. Then,

\(\sqrt{-15 - 8i}\) = x + iy

⇒ -15 – 8i = (x + iy)\(^{2}\)

⇒ -15 – 8i = (x\(^{2}\) - y\(^{2}\)) + 2ixy

⇒ -15 = x\(^{2}\) - y\(^{2}\) .................. (i)

and 2xy = -8 .................. (ii)

Now (x\(^{2}\) + y\(^{2}\))\(^{2}\) = (x\(^{2}\) - y\(^{2}\))\(^{2}\) + 4x\(^{2}\)y\(^{2}\)

⇒ (x\(^{2}\) + y\(^{2}\))\(^{2}\) = (-15)\(^{2}\) + 64 = 289

⇒ x\(^{2}\) + y\(^{2}\) = 17 ................... (iii) [x\(^{2}\) + y\(^{2}\) > 0]

On Solving (i) and (iii), we get

x\(^{2}\) = 1 and y\(^{2}\) = 16

⇒ x = ± 1 and y = ± 4.

From (ii), 2xy is negative. So, x and y are of opposite signs.

Therefore, x = 1 and y = -4 or, x = -1 and y = 4.

Hence, \(\sqrt{-15 - 8i}\) = ± (1 - 4i).


2. Find the square root of i.

Solution:

Let √i = x + iy. Then,

√i = x + iy

⇒ i = (x + iy)\(^{2}\)

⇒ (x\(^{2}\) - y\(^{2}\)) + 2ixy = 0 + i

⇒ x\(^{2}\) - y\(^{2}\) = 0 .......................... (i)

And 2xy = 1 ................................. (ii)

Now, (x\(^{2}\) + y\(^{2}\))\(^{2}\) = (x\(^{2}\) - y\(^{2}\))\(^{2}\) + 4x\(^{2}\)y\(^{2}\)

(x\(^{2}\) + y\(^{2}\))\(^{2}\) = 0 + 1 = 1 ⇒ x\(^{2}\) + y\(^{2}\) = 1 ............................. (iii), [Since, x\(^{2}\) + y\(^{2}\) > 0]

Solving (i) and (iii), we get

x\(^{2}\) = ½ and y\(^{2}\) = ½

⇒ x = ±\(\frac{1}{√2}\) and y = ±\(\frac{1}{√2}\)

From (ii), we find that 2xy is positive. So, x and y are of same sign.

Therefore, x = \(\frac{1}{√2}\) and y = \(\frac{1}{√2}\) or, x = -\(\frac{1}{√2}\) and y = -\(\frac{1}{√2}\)

Hence, √i = ±(\(\frac{1}{√2}\) + \(\frac{1}{√2}\)i) = ±\(\frac{1}{√2}\)(1 + i)






11 and 12 Grade Math 

From Root of a Complex Number to HOME PAGE




Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.



New! Comments

Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.